1990
DOI: 10.1302/0301-620x.72b4.2143192
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of the lumbosacral junction. Long-term follow-up of 26 cases

Abstract: Of 37 consecutive patients suffering from tuberculosis of the lumbosacral spine, 26 were reviewed after an average follow-up of 20 years. Those presenting at under 10 years of age usually had a discharging sinus or a pointing abscess and a visible kyphosis. In older patients, low back pain was the predominant presenting symptom. Neurological involvement was uncommon. Both operative and conservative treatment had resulted in fusion but all patients treated conservatively ended up with a kyphosis associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…6 Several large series have focused on tubercular lesion of the lumbosacral region (Bhojraj et al, 66 cases; Moon et al, 56 cases; Rajasekaran et al, 53 cases; Pun et al, 26 cases). [5][6][7][8] However, none of them have reported any case of spondylolisthesis either secondary to or coexisting with tuberculosis in the same patient. Pathological spondylolisthesis secondary to tuberculosis, or coexisting spondylolisthesis and spinal tuberculosis is an extremely rare occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Several large series have focused on tubercular lesion of the lumbosacral region (Bhojraj et al, 66 cases; Moon et al, 56 cases; Rajasekaran et al, 53 cases; Pun et al, 26 cases). [5][6][7][8] However, none of them have reported any case of spondylolisthesis either secondary to or coexisting with tuberculosis in the same patient. Pathological spondylolisthesis secondary to tuberculosis, or coexisting spondylolisthesis and spinal tuberculosis is an extremely rare occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The results of conservative treatment of tubercular spondylolisthesis with spinal braces and multidrug antitubercular chemotherapy are satisfactory and surgical stabilization is seldom needed. 2,5,6,8 …”
Section: Discussionmentioning
confidence: 99%
“…Fusion of the diseased area of the spine can be produced by non-operative treatment, but the kyphosis persists [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…49,57 Patients often present with pain, and neurologic dysfunction is uncommon. Kyphotic deformities are seen with some frequency.…”
Section: Figmentioning
confidence: 99%
“…While Moon et al report a relatively benign course in 56 adults treated by chemotherapy alone, 49 Pun et al found late pain and degenerative changes in more than 50% of patients, with significant kyphosis in 14 of 26 patients. 57 Compensatory lordosis in FIG. 9.…”
Section: Figmentioning
confidence: 99%